(untitled) - Kottelat, Maurine (Washington DC, 1996)
This freshwater biodiversity can be adversely affected by protects related to dams, flood control, water supply, mining, fisheries management, introduction of exotic species, irrigation, bridges, industrial effluent, domestic waste, waterway... and other purposes.
Keywords: Biological diversity; Sinh thái học